Respiratory Viral Infections in Patients With Cancer or Undergoing Hematopoietic Cell Transplant - Hijano, Diego R.; Maron, Gabriela; Hayden, Randall T. (Frontiers in Microbiology, 2018)
Survival rates for pediatric cancer have steadily improved over time but it remains a significant cause of morbidity and mortality among children. Infections are a major complication of cancer and its treatment. Community acquired respiratory viral infections (CRV) in these patients increase morbidity, mortality and can lead to delay in chemotherapy. These are the result of infections with a heterogeneous group of viruses including RNA viruses, such as respiratory syncytial virus (RSV), influenza virus (IV), parainfluenza virus (PIV), metapneumovirus (HMPV), rhinovirus (RhV) and coronavirus (CoV). These infections maintain a similar seasonal pattern to those of immunocompetent patients. Clinical manifestations vary significantly depending on the type of virus and the type and degree of immunosuppression, ranging from asymptomatic or mild disease to rapidly progressive fatal pneumonia Infections in this population are characterized by a high rate of progression from upper to lower respiratory tract infection and prolonged viral shedding. Use of corticosteroids and immunosuppressive therapy are risk factors for severe disease. The clinical course is often difficult to predict, and clinical signs are unreliable. Accurate prognostic viral and immune markers, which have become part of the standard of care for systemic viral infections, are currently lacking; and management of CRV infections remains controversial. Defining effective prophylactic and therapeutic strategies is challenging, especially considering, the spectrum of immunocompromised patients, the variety of respiratory viruses, and the presence of other opportunistic infections and medical problems. Prevention remains one of the most important strategies against these viruses. Early diagnosis, supportive care and antivirals at an early stage, when available and indicated, have proven beneficial. However, with the exception of neuraminidase inhibitors for influenza infection, there are no accepted treatments. In high-risk​ patients, pre-emptive treatment with antivirals for upper respiratory tract infection (URTI) to decrease progression to LRTI is a common strategy. In the future, viral load and immune markers may prove beneficial in predicting severe disease, supporting decision making and monitor treatment in this population.